Konsep Relasi Manusia Berdasarkan Pemikiran Martin Buber - Hia, Robeti (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
When moving from one place to another, people encounter a variety of things and persons. They encounter physical things, meet other people, and interact with them in a way that might be sensed as ‘divine’. The meanings emerging through human interactions in life appear when there is a presence of other human beings in the surrounding. Humans realise their meaningfulness within themselves when others find the same thing as well, that is, in realising the presence. Life turns into a meaningful experience when human beings treat their neighbours as a human being, and not as an object that does not react or respond when encountered. Regarding the others as a representation of our own relatedness with the divine may enable us respect human life, more than we value ourselves, for we realise that our relationship with fellow human beings is not the same as with objects around us. Our relation with the divine is situated in connectedness with other people so as to experience the beauty in relation. The divine needs humans not because he is weak, but because he has the desire to save and to make human’s life meaningful.